Successful Management in Unprovoked Upper Extremity Deep Vein Thrombosis: Case Report - Noverike, Nikhen; Kurnianingsih, Novi; Rizal, Ardian; Rahimah, Anna Fuji (Heart Science Journal, 2024)
BackgroundOne to four percent of all cases of deep vein thrombosis (DVT) occur in the upper extremities. Effective thrombolysis for upper extremity deep vein thrombosis (UEDVT) can be achieved with a combination of vascular interventions such as angioplasty, which is continued with catheter-directed thrombolysis (CDT) and anticoagulant therapy.Case IllustrationWe presented the case of a 40-year-old man who developed sudden pain and swelling in his right upper extremity. The thrombus was located in the right subclavian vein, confirmed by duplex ultrasonography. Laboratory results were normal. The patient was diagnosed with unprovoked UEDVT. He underwent venography, which showed an acute-on-chronic lesion at the right subclavian vein. We decided to use double access, tried to inflate the balloon to fragment the thrombus, several times of thrombo-suction, and then continued with Catheter-directed thrombolysis (CDT) using Alteplase. The patient continued oral anticoagulant therapy with Rivaroxaban. After 6 months of follow-up, there wasn’t any complaint. Evaluation of Duplex ultrasonography showed normal results without any recurrent thrombusConclusionThis case revealed how to treat acute-on-chronic lesions of unprovoked UEDVT with a comprehensive management method not only with balloon fragmentation and CDT but also anticoagulant therapy and showed a good outcome and no signs of bleeding complication.